French populism and discourses on secularism - Nilsson, Per-Erik 1981- (Bloomsbury Academic, 2019)
"Per-Erik Nilsson takes a religious studies approach to analyse French contemporary populism, and uses the discourse on secularism as a lens to do so. This book provides insight into the French and European far-right and radical-nationalist ideology and activism, and contributes to our understanding of the complex relationship between religion and the state in contemporary Europe and beyond. Marine Le Pen stated that secularism was a core value of the National Front, which signaled a significant shift in the far-right's rhetorical strategies and previous opposition to secularism. Nilsson argues that this conspicuous appropriation first came about as a logical result of the obsession of the established main-stream political parties and news media with questions of secularism, national identity, and Islam. He argues that a key player in understanding the National Front's change is the web-based journal Riposte Laïque, which has become a central actor in French radical-nationalist and anti-Islamic web and street based activism. For the first time, this source is examined in order to understand the French far-right's recent appropriation of secularism, as well as debates on secularism, national identity and Islam in France more broadly"...
Includes bibliographical references and index
Keywords: Secularism -- France; Populism -- France -- Religious aspects; Right-wing extremists -- France -- Religious aspects; Populismus; Säkularismus; Frankreich